THE CORRELATION BETWEEN EXTROVERT AND INTROVERT PERSONALITY TOWARD SPEAKING ABILITY OF THE EIGHTH GRADE STUDENTS IN SMPN 7 MENGWI IN ACADEMIC YEAR 2020/2021 - Ni Kadek Indah Damayanti; Ni Wayan Krismayani (Academic Journal on English Studies (AJOES), 2021)
The objective of this research was to find out the significant correlation between extrovertand introvert personality toward speaking ability of the eighth grade students in SMPN 7Mengwi. In conducting this research, the researcher has collected the data usingcorrelational research. The subjects of this research were 58 students of the eighth grade inSMPN 7 Mengwi in academic year 2020/2021. In collecting the data, the researcher used twoinstruments which were questionnaire for extrovert-introvert students, and speaking test forspeaking ability. The result showed the student with extrovert personality will get better scorein speaking ability meanwhile the students with introvert personality will get lower score inspeaking ability. Furthermore, the research instruments were made in order to collect thedata needed. The data were analyzed by using SPSS 25.0 that consist of Normality Test,Homogeneity Test, Pearson Product Moment, and T-Test. The alternative hypothesis wasaccepted. According to the result of Pearson Product Moment, it was found that was 0.649between extrovert personality and speaking ability, meanwhile 0.626 between introvertpersonality and speaking ability. It shows that there is correlation between extrovert andintrovert personality in students’ speaking ability.